Durio zibethinus rind as tyrosinase inhibitor for skin whitening agents in cosmetic products: RSM, COSMO-RS, PCA and molecular docking studies - Ismail, Sofiyyah; Shamsuri, Syamimi Sulfiza; Abdullah, Erna Normaya; Ahmad, Mohammad Norazmi (2020)
In this study, Response surface methodology (RSM) and Supercritical fuid extraction (SFE) were used to optimize the extraction of the polyphenols from Durio zibethinus rind. The optimized extraction variables conditions were found at at 5050 psi pressure, 60°C temperature and 80 min extraction time. Then Gas chromatography–mass spectrometry (GC-MS) and Principal component analysis (PCA) were used to identified and classify the major compound (Aspidospermidin-17-ol, 1-Acetyl-19, 21-Epoxy-15, 16-Dimethoxy; AP) as tyrosinase inhibitor, respectively. in the crude extract. Based on sigma profile in COSMO RS method, hydrogen bond plays a main role during the polyphenols extraction using carbon dioxide as a solvent. The DPPH method was used to study antioxidant properties of the extract with 37.85% scavenging activity. Molecular electrostatic potential (MEP) and molecular docking were done to identify and investigate the AP’s reactivity site and interaction that contribute to tyrosinase inhibition, respectively. Molecular docking simulation results indicated that AP in D. zibethinus presented their inhibitory mechanism mainly via van der Waals and π interaction.